Diskursus Influencer Kristen Dalam Misi Dan Penginjilan Kepada Native Digital - Joni Manumpak Parulian Gultom (Sekolah Tinggi Teologi Ekumene Jakarta., 2021)
The advancement of the virtual world has formed a generation of Native Digitals who are out of control, unhindered, and connected. The global world is presented freely with negative life values, meaningless and like without God. The use of quiet massive media technology every day for three hours 14 minutes per day can have ungood effects such as stress, depression, even not caring about spirituality. This generation is known to have experienced a major shift in the spiritual world, no longer believing in the existence of God. The question is how to solve the problem of native digital spirituality when churches with all forms of their ministry practices are no longer in demand? How do Christian influencers act in Native Digital outreach? And what kind of Mission and Evangelism can be done? The argument is that Christian influencers have a role and penetration capacity as an answer in missionary actions and evangelism to reach Native Digitals. Several steps of penetration [1] demonstrate the position of Christian influencers as extensions of church ministry in the media space. [2] Maximize mission and evangelism through a high degree of flexibility. [3] Preparation for ministry in a deep spiritual capacity. The purpose of this research is so that Christian influencers can play the highest role as spiritual media in Native Digital spiritual missions and outreach. The second thing is to become a liaison for the Church in the virtual world to bring this generation back to being connected to the local Church. Third, bring this generation to be saved. A research method is a qualitative approach with data collection through literature study and observation. It is aimed that through this research (1) new Christian influencers will emerge with spiritual content, (2) conversion and self-recovery of the digital generation will occur, (3) Christian influencers integrated with local churches..